Nutritional status of adults in Northwest Argentina: an observational study - Andrade, Lautaro Daniel (2022)
Background: Northwestern Argentina (NWA) is a region with geographic, ethnic, socioeconomic, and cultural characteristics that set it apart from the rest of the country. The present study aimed to analyze both the anthropometry and nutritional status of adults in this region and establish its recent secular trend. Methods: This was an observational cross-sectional study that utilized the National Risk Factor Survey (NRFS) 2018. We calculated the body mass index (BMI), waist-to-height ratio (WHtR), and relative fat mass (RFM) by sex in the six provinces that comprise the NWA region based on the weight, height, and waist circumference data of 3,283 individuals. We also calculated the prevalence of underweight, overweight, and obesity. Furthermore, we evaluated the correlation and correspondence between measurements and anthropometric indexes. Joinpoint regression analyses were performed to identify trend changes, which were then compared with that established for the rest of the country. Results: The regional population presented a heterogeneous distribution of anthropometric variables, in which the Andean provinces of Salta and Jujuy presented the lowest height and weight and highest percentage of body fat. These anthropometric differences were not evident in the prevalence of nutritional status determined by the BMI, which did not exhibit significant variations between the region and the rest of the country. Excess body weight, as measured by any of the indexes, reached over 65% of the population, and the prevalence of obesity in both sexes was higher than that established for Argentina overall. The secular trend in obesity was positive and higher in some provinces compared to the region and the rest of the country. These differences are interpreted according to the geographic, ethnic, socioeconomic, and cultural characteristics of the region. Conclusions: The anthropometric variables registered in some provinces vary significantly compared to those of the country as a whole, and these differences are not captured by the traditionally used obesity indices.